2011
DOI: 10.1158/0008-5472.can-10-3604
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Instability Confers Intrinsic Multidrug Resistance

Abstract: Aneuploidy is associated with poor prognosis in solid tumors. Spontaneous chromosome missegregation events in aneuploid cells promote chromosomal instability (CIN) that may contribute to the acquisition of multidrug resistance in vitro and heighten risk for tumor relapse in animal models. Identification of distinct therapeutic agents that target tumor karyotypic complexity has important clinical implications. To identify distinct therapeutic approaches to specifically limit the growth of CIN tumors, we focused… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
359
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(388 citation statements)
references
References 47 publications
16
359
2
Order By: Relevance
“…MN micronucleus, NPB nucleoplasmic bridge, NBUD nuclear bud MB cells, as described by Cohen et al (2004). Moreover, Roschke et al (2003), analyzing 59 cancer cell lines, have found association between structural complexity of karyotype and modal chromosome number, which can be strongly driven by CIN (Lee et al 2011). In our study, we found that both MB cell lines showed a significant number of NCCAs and a high chromosomal heterogeneity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…MN micronucleus, NPB nucleoplasmic bridge, NBUD nuclear bud MB cells, as described by Cohen et al (2004). Moreover, Roschke et al (2003), analyzing 59 cancer cell lines, have found association between structural complexity of karyotype and modal chromosome number, which can be strongly driven by CIN (Lee et al 2011). In our study, we found that both MB cell lines showed a significant number of NCCAs and a high chromosomal heterogeneity.…”
Section: Discussionsupporting
confidence: 81%
“…UW473 cells were relatively more sensitive to CDDP, MTX, and TMZ treatments and more resistant to DX than UW402 cell line. Although it has been largely described that CIN confers intrinsic multidrug resistance in tumors (Sheltzer and Amon 2011;Lee et al 2011) and consequently poorer prognosis in cancer patients (Carter et al 2006), in our study, UW473 showed a greater CIN phenotype and it was more chemosensitivity than UW402, which could confirm the hypothesis that excessive genomic instability may surpass a threshold compatible with cell viability (Cahill et al 1999). This concept has been recently corroborated in the clinical context through studies reporting a paradoxical relationship between CIN and survival outcome in cancer, being that tumors exhibiting extreme CIN displayed improved prognosis relative to tumors with intermediate levels of CIN Roylance et al 2011;McGranahan et al 2012;Lee and Swanton 2012).…”
Section: Discussionsupporting
confidence: 76%
“…CIN is associated with poor patient prognosis, and various studies have shown that it correlates with advanced tumor stage including acquisition of metastatic potential and drug resistance (3)(4)(5). It has been proposed that by frequently changing the karyotype of tumor cells, that CIN provides an agent of change that drives the evolution of tumor cell phenotypes (3)(4)(5)(6)(7)(8). The treatment difficulties encountered in advanced stage tumors underscores the importance of determining the mechanisms of CIN and how they contribute to tumor growth.…”
mentioning
confidence: 99%
“…The various compositions arising from the meiosis could lead to chromosome combinations that provide a compensation of the imbalances. Moreover, aneuploid cells might be chromosomally unstable, thus allowing continuous "reinvention" of the karyotype composition during various drug treatments, a phenomenon that resembles the enhanced resistance acquisition in chromosomally unstable composite aneuploid cancer cells [5] [53]. Further investigations should address the mechanisms of the increased fitness in aneuploid cells.…”
Section: Benefits Of Aneuploidymentioning
confidence: 99%